KARDIOCHIRURGIA DOROSŁYCHEmergency invasive intervention in the diagnosis and treatment of perioperative ischaemia in patients undergoing coronary surgery - Kowalik, Violetta; Wasilewski, Jarosław; Hudzik, Bartosz; Szafron, Bartłomiej; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduce: Perioperative myocardial infarction after surgical coronary artery revascularization is an important diagnostic and therapeutic issue. Urgent coronary and bypass angiography is a relatively new strategy, but there are few publications on this subject. Aim: The aim of this study is to present the results of urgent diagnostic angiography and percutaneous interventions in patients with symptoms of acute myocardial ischaemia during the first 24 hours after coronary artery bypass graft surgery. Material and Methods: The study group comprised 153 (1.38%) among 11 090 patients who underwent coronary artery surgery. They underwent early coronary and bypass angiography due to the symptoms of acute myocardial ischaemia. Results: On the basis of angiography percutaneous intervention was performed in 62 (40.5%) pts, including balloon angioplasty of native artery or bypass in 23 (37.1%) pts and 39 (62.9%) pts had angioplasty with stent implantation. In 30 (19.6%) cases angiography revealed no new lesions in native arteries or grafts. 42 (27.4%) pts were qualified for conservative therapy, because of lack of technical possibilities for PCI or reoperation. Surgical reintervention was needed in only 25 (16.3%) pts. Conclusions: The diagnostic and therapeutic strategy of urgent angiography of coronary arteries and grafts in the event of perioperative ischaemia after coronary artery surgery (in the first 24 hours after operation) allows the precise diagnosis and establishment of optimal management. In more than 40% of pts percutaneous intervention is possible with a high success rate (above 85%). 80% of patients with acute perioperative ischaemia can avoid reoperation and those referred for repeat cardiac surgery had established indications and the range of reintervention.